Musykilât Ta’lîm al-Ashwâth al-‘Arabiyyah li Ghair al-Nâthiqîn bihâ wa Tharîqah Hillihâ fî Ta’lîmihâ - Shofil Fikri (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2020)
This paper aims to describe the problems in learning phonology, various phonetic problems, the cause of their occurrence and how to overcome them. This paper is a qualitative descriptive study with the type of literature review from which the results of scientific research or other books are closely related to the learning of phonology knowledge, problems and ways to overcome them which are then explained descriptively. The results of this paper conclude that: 1) learning phonology in Arabic is very important to teach at the beginning of the teaching of Arabic because errors in saying a word affect the true or meaningless; 2) There are two main problems in general teaching phonology for non-Arab students, namely: problems relating to the direction of education and problems related to linguistic systems that include phonetic errors and pronunciation of a letter and word; 3) The cause of the problem is because it is influenced by the use of mother tongue (first language) in general, so that it cannot distinguish the length or short of a tone, the pronouncement of self-determination letters, pronunciation of syamsiyah and qamariyah letters, pronunciation of letters of the same nature and pronunciation tanwin letters; 4) As for the solutions offered in overcoming the phoneme pronunciation problem are: proactively instructors should develop children's fluency in speaking phonemes, indoctrinate sound sounds in listening and speaking activities, obtain language sounds in reading and writing activities, and design teaching processes through practical training in tongue sports to gain phoneme skills.